A construção metapsicológica do Sinthoma na obra lacaniana a partir da escrita de James Joyce - Freire, Joyce Marly Gonçalves; Pereira, Mário Eduardo Costa; da Silva, Luiz Carlos Avelino [UNESP] (My University, 2014)
This article aims to discuss the Sinthome’s metapsychological construction on Lacanian work, from the way the subjective position of James Joyce structure: the tireless work around of his name recognition – the father’s name – and the publication of his work. This name’s construction bypasses the foreclosure actually by Joyce’s life and Lacan’s reflections make it a paradigm for to think about the possible psychoanalytic work in psychosis, as well as on the question of the analysis’s end. It reflects on some seminars of Lacan’s work in relation to the issue of clinical psychosis, especially the seminar The sinthome.
The metapsychological construction of the Sinthome in Lacan through the writing of James Joyce
Keywords: Foreclosure; Literature; Psychosis; Sinthome